2019
DOI: 10.1016/j.bbmt.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

FLT3-ITD and CEBPA Mutations Predict Prognosis in Acute Myelogenous Leukemia Irrespective of Hematopoietic Stem Cell Transplantation

Abstract: Cytogenetic and genetic changes have prognostic significance in acute myelogenous leukemia (AML). In our study, we compared the cytogenetic changes and gene mutations (NPM1, CEBPA, DNMT3A, FLT3-ITD, FLT3-TKD, and C-KIT) with clinical outcomes in 1132 patients with AML enrolled at our center over a 10-year period. A total of 977 patients provided gene mutation data. There were subsets of patients who exhibited mutations in NPM1 (17.9%), CEBPA (16.4%), FLT3-ITD (18.5%), FLT3-TKD (3.9%), DNMT3A (8.6%), and C-KIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Our survival analysis showed that FLT3/ITD mutation was identified for inferior EFS and OS rates compared with FLT3/ITD wild‐type, and receipt of SCT was correlated with improved EFS and OS when compared with those who did not receive SCT. These findings are consistent with the concept that SCT is indicated for FLT3/ITD mutations AML patients 34,35 . In the current research, CEBPA mutations were frequent in patients with normal karyotype and were more common combined with FLT3‐ITD wild‐type.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our survival analysis showed that FLT3/ITD mutation was identified for inferior EFS and OS rates compared with FLT3/ITD wild‐type, and receipt of SCT was correlated with improved EFS and OS when compared with those who did not receive SCT. These findings are consistent with the concept that SCT is indicated for FLT3/ITD mutations AML patients 34,35 . In the current research, CEBPA mutations were frequent in patients with normal karyotype and were more common combined with FLT3‐ITD wild‐type.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with the concept that SCT is indicated for FLT3/ITD mutations AML patients. 34,35 In the current research, CEBPA mutations were frequent in patients with normal karyotype and were more common combined with FLT3-ITD wild-type. In recent years, some studies [36][37][38] had demonstrated that coexistence of CEBPA and FLT3/ITD mutations confers inferior outcomes in several large cohort adult AML cases.…”
Section: Discussionmentioning
confidence: 67%
“…In the entire study, our analysis showed that SCT recipients of mutant FLT3/ITD could significantly improve EFS and OS when compared with those who did not receive SCT. These findings were consistent with the concept that SCT was indicated for AML patients with FLT3/ITD mutation 32 , 33 . When we focused on the impact of FLT3/ITD AR on the clinical outcome in pediatric AML, especially in the subgroup of chemotherapy-only patients, high FLT3/ITD AR was apparently associated with poorer EFS and OS when compared with low AR.…”
Section: Discussionsupporting
confidence: 91%
“…Among those recurrent gene mutations, the most adverse prognosis was observed in patients with DNMT3A and FLT3-ITD co-mutation, whose survival could be significantly improved with allo-HSCT [7,34]. Recurrent gene mutations analysis showed JAK2, FLT3-ITD high , and KIT high mutations were identified as significant prognostic factors for OS in multivariate analysis [35].…”
Section: Flt3mentioning
confidence: 99%